Acute hyperparathyroid crisis: ectopic submandibular parathyroid gland the culprit - Unais T, M (Ann R Coll Surg Engl, 2021)
Parathyroid exploration via a focused approach or bilateral neck exploration should be considered in the management of all types of hyperparathyroidism. Eutopic and ectopic, single or multiple glands can pose challenges to the surgeon and available preoperative imaging modalities may not be equally applicable or appropriate in all cases. We report an interesting case of parathyroid surgery where the patient presented with a rare ectopic adenoma in the form of a hyperparathyroid crisis.